2014
DOI: 10.13054/mije.14.15.4.2
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Writing Dispositions of 6th Grade Students in terms of Different Variables

Abstract: This research was conducted with an aim to analyze the writing dispositions of the 6 th grade students in terms of different variables. The research was carried out based on the descriptive survey model. The participants of the research are composed of a total of 672 students as 342 male students and 330 female students from Ankara, Balıkesir, Bartın, Adana, and Kayseri. The research data were obtained by the application of "Personal Information Form" developed by the researchers and "Writing Disposition Scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…According to Piazza and Siebert (2008), disposition is like "a broad construct within the affective domain in which writers bring to their writing such resources as selfdiscipline, perseverance in the face of difficulties, tolerance of ambiguity, autonomy, willingness to take risks, motivation, self-efficacy, and interest" (p. 275). According to Tabak and Topuzkanamis (2014), disposition is a psychological term that expresses a way of acting voluntarily and consciously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Piazza and Siebert (2008), disposition is like "a broad construct within the affective domain in which writers bring to their writing such resources as selfdiscipline, perseverance in the face of difficulties, tolerance of ambiguity, autonomy, willingness to take risks, motivation, self-efficacy, and interest" (p. 275). According to Tabak and Topuzkanamis (2014), disposition is a psychological term that expresses a way of acting voluntarily and consciously.…”
Section: Introductionmentioning
confidence: 99%
“…Although some research related to writing disposition on a national scale has been found in the literature (Avcı & Iseri, 2014;Bas, 2012;Iseri & Unal, 2010;Tabak, 2014), the number of writing disposition-based studies is not comparable to that of writing anxiety based research on an international scale (Pytash & Li, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Zorbaz [43] detected that girls enjoyed writing more, and the boys had higher writing anxiety than the girls. Işeri [28], Baş and Şahin [7], Tabak and Topuzkanamış [36], and Uçgun [39] detected in their researchers that writing dispositions of girls were in a more positive level compared to boys.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…They are repeated and habitual pattern of behavior, rather than a one-time occurrence. They are not a static characteristic of personality; they can be nurtured and changed (Cocuk, Yelken, Ozer;Tabak & Topuzkanamis, 2014).…”
Section: Expository Writingmentioning
confidence: 99%
“…Accordingly, a few number of studies address writing dispositions and they can be classified into four different strands of research.The first strand of research either reported the development and validation of the Writing Dispositions Scale (WDS) (Piazza & Siebert, 2008) or reported how to adapt this scale to different contexts (Işeri & Ünal, 2010). Based on these studies, Writing Disposition Scale is found valid and reliable and it is the only research instrument known to assess writing dispositions.The second set of studies explored the nature of writing dispositions either qualitatively by analyzing students' narrations about them (Reid, 2017) or quantitatively through applying WDS to evaluate students' writing dispositions (Irseri, 2010;Mcclenny, 2010;Pytash & Li, 2014;Tabak & Topuzkanamis, 2014;Unal, 2010).…”
Section: Expository Writingmentioning
confidence: 99%